Implementasi Kompetensi Pedagogik Guru Dalam Perancangan Dan Pelaksanaan Pembelajaran - Amris, Firda Khairati; Hankam, Arief Arafat (Institut Agama Islam Sumatera Barat Pariaman, 2023)
The issue that this study will address is knowing the teacher's ability to prepare learning plans. The aim of this research is to find out which pedagogical competencies they possess ultimately influence the learning process. The research methodology used in this study is a literature review. The information used in this study takes the form of sources obtained from relevant articles that will be reviewed, such as Google Scholar. Data collection can be in the form of keywords used to search for articles to be reviewed. The keywords that researchers used when researching articles were